Research Quality and Newsworthiness of Published Articles are Partial Predictors of Journal Impact Factors - Martin, Jason (Evidence Based Library and Information Practice, 2012)
Objective – Determine what characteristics of a journal’s published articles can be used to predict the journal impact factor (JIF). Design – A retrospective cohort study. Setting – The researchers are located at McMaster University, Hamilton, Ontario, Canada. Subjects – The sample consisted of 1,267 clinical research articles from 103 evidence based and clinical journals which were published in 2005 and indexed in the McMaster University Premium LiteratUre Service (PLUS) database and those same journals’ JIF from 2007. Method – The articles were divided 60:40 into a derivation set (760 articles and 99 journals) and a validation set (507 articles and 88 journals). Ten variables which could influence JIF were developed and a multiple linear regression was run on the derivation set and then applied to the validation set. Main Results – The four variables found to be significant were the number of databases which indexed the journal, the number of authors, the quality of research, and the “newsworthiness” of the journal’s published articles. Conclusion – The quality of research and newsworthiness at time of publication of a journal’s articles can predict the journal impact factor with 60% accuracy.